2012
DOI: 10.1007/s12032-012-0316-7
|View full text |Cite
|
Sign up to set email alerts
|

A coincidence of renal cell carcinoma and hematological malignancies

Abstract: Hematological malignancies with renal cell carcinoma (RCC) are rarely seen. We reported here two cases of coincidence of RCC with multiple myeloma (MM) and Hodgkin's disease (HD). A 69-year-old male patient with tumor that was located at the upper pole of left kidney was admitted to our clinic. Partial tumoral resection was performed and stage-I RCC was diagnosed after the histopathological examination of tumor. Moreover, he was diagnosed with IgG kappa stage-IIA MM as a result of bone marrow examination and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
5
0
2
Order By: Relevance
“…There is also an increased risk of RCC in patients with NHL that may be attributed to chemotherapy and radiation used in NHL treatment[ 2 , 3 , 11 , 12 ]. Additional etiologies for concurrent RCC and HM include viruses such as Epstein-Barr virus, Helicobacter pylori , and human T-lymphotropic virus-1 that have been implicated in lymphomas and carcinomas[ 2 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also an increased risk of RCC in patients with NHL that may be attributed to chemotherapy and radiation used in NHL treatment[ 2 , 3 , 11 , 12 ]. Additional etiologies for concurrent RCC and HM include viruses such as Epstein-Barr virus, Helicobacter pylori , and human T-lymphotropic virus-1 that have been implicated in lymphomas and carcinomas[ 2 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been proposed to account for concurrent RCC and HM, including genetic mutations common to both RCC and HM, hormonal or environmental factors, viral infections, prior cytotoxic chemotherapy or radiation for malignancy, and immune dysregulation[ 2 , 3 , 5 , 8 - 12 ]. It has been suggested that the first malignancy predisposes to the second through an immunomodulatory effect[ 1 - 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our patient had synchronous malignencies. The other case was a 53-year-old male patient diagnosed with RCC 4 years prior to Hodgkin's disease (Ann-Arbor, stage II-B) [3]. And, the third was 69-year-old male patient, diagnosed with multiple myeloma (IgG, κ, stage II-A) and RCC of left nephrectomy specimens, synchronously [3].…”
mentioning
confidence: 99%
“…The other case was a 53-year-old male patient diagnosed with RCC 4 years prior to Hodgkin's disease (Ann-Arbor, stage II-B) [3]. And, the third was 69-year-old male patient, diagnosed with multiple myeloma (IgG, κ, stage II-A) and RCC of left nephrectomy specimens, synchronously [3]. Interestingly, unlike our patient, Choueiri et al reported case series of MM and RCC on the right side with right renal involvement except for one [5].…”
mentioning
confidence: 99%
“…W literaturze są opisy innych przypadków współwystępowania PCM i RCC (tab. 1) [5,[9][10][11][12][13][14].…”
unclassified